2020
DOI: 10.1097/ncm.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Care Models for High-Need, High-Cost Adults in the United States

Abstract: Purpose of Study: This scoping review explored research literature on the integration and coordination of services for high-need, high-cost (HNHC) patients in an attempt to answer the following questions: What models of transitional care are utilized to manage HNHC patients in the United States? and How effective are they in reducing low-value utilization and in improving continuity? Primary Practice Settings: U.S. urban, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Use of telehealth for case management and care coordination in US rural settings is receiving increased policy emphasis due to older adults’ higher rates of poverty, chronic conditions, and age-adjusted mortality for all causes in these settings, particularly during COVID-19 (Department of Health and Human Services, 2020; National Academies of Sciences, Engineering, and Medicine, 2021; National Advisory Committee on Rural Health and Human Services, 2019). Nursing care management models such as the Transitional Care Model (Assessing/Managing Risks and Symptoms) may be able to incorporate modified Fried screening to better monitor older adult symptoms to prevent poor functional outcomes across a wide range of rural and urban clinical settings and health system care model designs to achieve improved health equity outcomes (Hewner et al, 2021; Hirschman et al, 2015; National Academies of Medicine, 2017; National Academies of Sciences, Engineering, and Medicine, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Use of telehealth for case management and care coordination in US rural settings is receiving increased policy emphasis due to older adults’ higher rates of poverty, chronic conditions, and age-adjusted mortality for all causes in these settings, particularly during COVID-19 (Department of Health and Human Services, 2020; National Academies of Sciences, Engineering, and Medicine, 2021; National Advisory Committee on Rural Health and Human Services, 2019). Nursing care management models such as the Transitional Care Model (Assessing/Managing Risks and Symptoms) may be able to incorporate modified Fried screening to better monitor older adult symptoms to prevent poor functional outcomes across a wide range of rural and urban clinical settings and health system care model designs to achieve improved health equity outcomes (Hewner et al, 2021; Hirschman et al, 2015; National Academies of Medicine, 2017; National Academies of Sciences, Engineering, and Medicine, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…16 Many models focus on care coordinators' efforts to stabilize care transitions in populations that have highrisk conditions, such as congestive heart failure, or in complex patients during major care transitions between organizations, such those occurring between hospitals and skilled nursing facilities. 17 Other care transition models focus primarily on harnessing transitional data for the purpose of cross-agency communication in the form of care alerts. 5 2) "In partnership with other healthcare professionals, registered nurses have demonstrated leadership and innovation in the design, implementation, and evaluation of successful team-based care coordination processes and models.…”
Section: Concept Analysismentioning
confidence: 99%
“…Previous studies have supported the segmentation of high-cost health care users on the basis of prior healthcare utilization patterns [ 7 ], complex medical conditions [ 9 ], high cost [ 10 ], or a combination of these factors [ 11 ]. A concept analysis identified three main subgroups of high-cost health care users: adults with multiple chronic conditions and functional disability, the frail elderly, and patients under 65 years old with behavioral health condition or disabled [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A concept analysis identified three main subgroups of high-cost health care users: adults with multiple chronic conditions and functional disability, the frail elderly, and patients under 65 years old with behavioral health condition or disabled [ 12 ]. Another scoping review and gap analysis focused on transitional care models for high-need, high-cost adults to reduce low-value utilization [ 11 ]. Figueroa et al [ 13 ] identified two high-need, high-cost patient personas across 11 developed countries, using accessible patient-level datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation